Kenya's submission on progress, challenges, gaps and priorities in implementing the gender action plan to inform the review of the implementation of the enhanced Lima work programme on gender and its gender action plan - Republic of Kenya (2024)
Kenya takes this opportunity to submit her views pursuant to Decision 15/CP.28 paragraph 2 that Invited Parties, UN entities, UNFCCC constituted bodies and relevant organizations to submit their inputs on progress, challenges, gaps and priorities in implementing the gender action plan, categorized by deliverable or output for each activity under the gender action plan, and on future work to be undertaken on gender and climate change, to inform the review of the implementation of the Enhanced Lima Work Programme on gender and its Gender Action Plan.